"Translate me, but don't translate me": Challenges of religious text translation: a case study*. Issue 2 (4th May 2017) - Hemmat, Amrollah
Abstract: Sacred text says "translate me but don't translate me" as Jacques Derrida cites. This wittingly articulated adage marks the complexity and ultimately utopian nature of translating religious texts, texts communicating transcendental concepts. Furthermore, sacred text possesses rhetorical qualities that make its translation unique and challenging. Exerting authority, inducing awe and wonder, enchanting, motivating, and transforming hearts are among distinct characteristics of such texts that need to be faithfully transferred into the target language and culture. This paper uses a case study to demonstrate methods adopted for faithful translation of a religious text. This collaborative approach to translation can serve as a prototype for any translation task challenging in nature.